KARAKTERISTIK BRAND COMMUNITY DAN IMPLIKASINYA PADA LOYALITAS: STUDI KASUS ATAS KOMUNITAS XBOX DAN PLAYSTATION VGI INDONESIA - , Dody Rachmatullah Syahhery Iskawijar ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The tight of competitive market lately make video game company must protect their consumer loyalty. So many brand community that community based on video game, Microsoft and Sony believed that community is future potential market. The problem is consumer loyalty on some brand is needed by a company to survive on market. With brand community Microsoft and Sony can protect their loyalty consumer. This research will analyze characteristic of brand community and implication of loyalty. This research using qualitative methods. Methods for collecting the data using focus group discussion and in-depth interview. The function of this methods are to know much more about characteristic in community and how the implication loyalty on Xbox and Sony VGI community. Total of respondent is about 40 member of each community. The result show that characteristic on brand community like oppositional brand loyalty, legitimacy, celebrating brand stories, sharing brand stories, integration and retaining member, assisting in the use of the brand will help the member of community. The other result show how the implication loyalty in Xbox and Sony VGI community Indonesia.